Eye Socket Regeneration and Reconstruction. (3rd March 2020) - Borrelli, M.; Geerling, G.; Spaniol, K.; Witt, J.
ABSTRACT: Purpose: When an eye has become irreversibly blind or painful it is removed by enucleation or evisceration. The resulting anophthalmic socket usually receives a volume replacing implant and is subsequently fitted with a prosthetic shell for adequate cosmesis. Trauma, tumour or immunological pathomechanisms can induce loss of bone, orbital soft tissue volume, and conjunctival contraction or implant exposure, which result in difficult or impossible prosthesis wear. In this situation as well as in numerous diseases limited to the conjunctiva (e.g. Pterygium, or cicatrizing conjunctivitis) strategies to substitute the lost tissue are required. Methods: A review of the literature search using various electronic databases (PubMed and MEDLINE) was performed on indications, surgical techniques and materials used to restore the ocular socket. Results: Amniotic membrane and oral mucosa are still the most commonly used substitutes for the reconstruction of larger conjunctival defects and ocular socket reconstruction. However, due to limitations of clinical available grafts, synthetic scaffolds, biomaterials or tissue-engineered grafts have been described in preclinical studies but most of them have not been investigated adequately in clinical studies yet. In orbital volume replacement, porous and nonporous spheres are used and both show acceptable results. However, more clinical studies are required that directly compare the outcomes in patients with similar conditions. Dermofat graft remains a good option in case of sockets with significant orbital volume and conjunctival surface loss. Conclusion: Beyond established techniques using autologous or allogeneic tissue, various approaches of engineering tissue based on scaffolds and stem cell expansion techniques are currently under investigation and may become alternatives in socket reconstruction in the not too far future.